Partial cointegrated vector autoregressive models with structural breaks in deterministic terms - Takamitsu Kurita; Bent Nielsen (Econometrics, 2019)
This paper proposes a class of partial cointegrated models allowing for structural breaks in the deterministic terms. Moving-average representations of the models are given. It is then shown that, under the assumption of martingale difference innovations, the limit distributions of partial quasi-likelihood ratio tests for cointegrating rank have a close connection to those for standard full models. This connection facilitates a response surface analysis that is required to extract critical information about moments from large-scale simulation studies. An empirical illustration of the proposed methodology is also provided.
Keywords: C12; C32; C50; 330; cointegrating rank; deterministic terms; partial cointegrated vector autoregressive models; response surface; structural breaks; weak exogeneity